Study on Structure Characteristic and Operating Parameter Interval of High-speed Multi-feature Gear Shaft - Zhang Kun Xu Wenbo Mao Jizhe Wang Xiaopeng (Jixie chuandong)
Based on the concept of forward engineering design, a fast static-dynamic joint design method is proposed to study the mechanical properties and the range of design and operation parameters of the structure of high-speed multi-feature gear shafts. The safety factor of dangerous interface is used to check the strength of shaft, and the ratio of three safety factor, i.e. contact strength of tooth surface, bending strength of tooth root and dangerous interface, is weighed to calculate the operating parameter interval under static condition. The natural frequency and displacement modes of multi-feature gear shafts, and the Cambell damping diagram, and the relationship between the accuracy of dynamic balance and the response of rotational speed and vibration amplitude are output by dynamics analysis. Finally, the reliable parameter intervals of multi-feature gear shafts can be obtained by the fusion of static and dynamic parameters intervals, which can provide auxiliary design support for the development of new multi-feature shafts in engineering applications.